Hamilton-Jacobi formalism on the null-plane: Applications - Bertin, M. C. [UNESP] (2009)
In this work we discuss the Hamilton-Jacobi formalism for fields on the null-plane. The Real Scalar Field in (1+1) - dimensions is studied since in it lays crucial points that are presented in more structured fields as the Electromagnetic case. The Hamilton-Jacobi formalism leads to the equations of motion for these systems after computing their respective Generalized Brackets. Copyright © owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.